Telemedicine in the Post-Pandemic Era: Market Trends, Clinical Impact, Challenges, and the Road Ahead - Jain, Vipul; Bansal, Mamta; Yogender, Yogender; Harshpal, Harshpal; Riya, Riya; Ankita, Ankita; Mansi, Mansi; Rajat, Rajat; Manisha, Manisha (Journal of Neonatal Surgery, 2025)
Rising throughout COVID-19 and still changing treatment is telemedicine, the remote delivery of healthcare via digital technology. Reviewing telemedicine's market growth, uses, advantages, obstacles, and case studies would help one to suggest worldwide optimizing tactics. Methods: Using PubMed, Scopus, WHO, and market-research reports (2020–2025), a narrative review was undertaken. Extracted and synthesized were data on market size, clinical results, and implementation challenges. Global telemedicine market expected reach USD 364–709 billion by 2031–2034 (CAGR 11–18%), anticipated to be USD 115–135 billion in 2023 Applications of telemedicine include primary care, specialist consultations, remote monitoring, and mental health services. Reduced readmissions, heart failure (mortality risk ↓40%), and diabetes (HbA1c) demonstrate better results in meta-analyses. Technology access gaps, legislative fragmentation, clinical restrictions, and data protection issues comprise some of the obstacles. Case studies: US Medicare exemptions sped up adoption; eSanjeevani from India provided 16 million+ consultations; sub-Saharan Africa pilots encountered connection challenges. Though it needs interpretability frameworks, artificial intelligence integration is ready to automate triage and improve diagnosis.